Investigation of Thermophysical Parameters Properties for Enhancing Overpressure Mechanism Estimation. Case Study: Miri Area, West Baram Delta - Adha, K. (Institute of Physics Publishing, 2017)
Determining the pore pressure data and overpressure zone is a compulsory part of oil and gas exploration in which the data can enhance the safety with profit and preventing the drilling hazards. Investigation of thermophysical parameters such as temperature and thermal conductivity can enhance the pore pressure estimation for overpressure mechanism determination. Since those parameters are dependent on rock properties, it may reflect the changes on the column of thermophysical parameters when there is abnormally in pore pressure. The study was conducted in "MRI 1" well offshore Sarawak, where a new approach method designed to determine the overpressure generation. The study was insisted the contribution of thermophysical parameters for supporting the velocity analysis method, petrophysical analysis were done in these studies. Four thermal facies were identified along the well. The overpressure developed below the thermal facies 4, where the pressure reached 38 Mpa and temperature was increasing significantly. The velocity and the thermal conductivity cross plots shows a linear relationship since the both parameters mainly are the function of the rock compaction. When the rock more compact, the particles were brought closer into contact and making the sound wave going faster while the thermal conductivity were increasing. In addition, the increment of temperature and high heat flow indicated the presence of fluid expansion mechanism. Since the shale sonic velocity and density analysis were the common methods in overpressure mechanism and pore pressure estimation. As the addition parameters for determining overpressure zone, the presence of thermophysical analysis was enhancing the current method, where the current method was the single function of velocity analysis. The presence of thermophysical analysis will improve the understanding in overpressure mechanism determination as the new input parameters. Thus, integrated of thermophysical technique and velocity analysis are important parameters in investigating the overpressure mechanisms and pore pressure estimation during oil and gas exploitation in the future. © Published under licence by IOP Publishing Ltd.